Managing for results - THIDA, Win (KDI School, 2017)
This study examines the effectiveness of foreign aid in Myanmar especially in health sector. This study also examines the relationship between foreign aid and infant mortality rate of Myanmar, Cambodia and Viet Nam for 2002 -2015. The empirical results show that there is negative relationship between foreign aid and infant mortality rate. The foreign aid can be effective with sound governance and lower rate of corruption. Infant mortality rate can be reduced with good sanitation facilities and decreasing number of HIV/AIDS addicted person. This study uses the SPSS regression method for analyzing the relationship between factors.
Thesis(Master) --KDI School:Master of Public Policy,2017